Comparison of bupivacaine versus bupivacaine-dexamethasone infiltration for postoperative analgesia in skin graft donor sites: a randomized trial - Ramy Mahrose; Ahmed Mohammed Elsayed; Asmaa Adel Sabry (Ain Shams Journal of Anesthesiology, 2020)
Abstract Background Skin grafting, both partial and complete thickness, is frequently used in reconstruction of traumatic soft tissue defects. It is of great value not only for functional and anesthetic purposes in the field of plastic surgery, but also for other surgical specialties. Of all the problems in the early postoperative period, pain is considered the most important, ameliorating it can lead to significant reduction in postoperative morbidity and faster recovery of the skin donor site. Objective To evaluate use of dexamethasone as adjuvant for bupivacaine in subcutaneous local anesthesia infiltration for skin graft donor sites, on quality of pain relief and total dose of analgesic requirements in the early hours postoperatively. Methods Ninety-five patients were randomly allocated to receive local bupivacaine infiltration (group LB) (48 patients), or dexamethasone plus bupivacaine (group LB + D) (47 patients) in skin donor site after skin harvesting. In addition to basic demographic data, patients were compared for numerical rating scale (NRS), total dose of morphine including morphine equivalents, time to 1st breakthrough pain (over an observational period during the first 12 h postoperatively) and duration of surgery. Results Numerical rating scale figures were significantly better (P < 0.05) in group (LB + D) than group (LB) in the first 7 h postoperatively. Likewise, consumption of morphine or its equivalents was considerably less, as well as time to first breakthrough pain. Duration of surgery was not significantly different between both groups. Conclusion Addition of dexamethasone to bupivacaine provided effective analgesia for patients undergoing skin grafting surgery, with less need for rescue analgesia in the early postoperative period to bupivacaine alone.